Mineral deficiencies of cattle in Paiaguás region in Pantanal Mato-grossense. I.Calcium, phosphorus and magnesium - Brum, Paulo A. R. de; Sousa, Júlio C. de; Comastri Filho, José A.; Almeida, Irajá L. de (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out in order to survey soil defficiency on calcium (Ca), phosphorus (P) and magnesium (Mg), either in forage or in animal tissues, during four different periods of the year, in the region of Paiaguás, lowlands of Mato Grosso State, Brazil. Calcium present in the soil, indifferent on geomorphic units and forage species, ranged through the year from 0.057 to 0.170 meq/100 g of soil, 0.13% to 0.24% in forages, 33.67% to 36.88% in bone P, ranged from 1.6 ppm to 5.16 ppm, in the soil 0.07% to 0.15% forages, 2.59 to 4.38 mg/100 ml in blood serum; 14.12% to 16.64% in bone. Mg ranged from 0.032 to 0.055 meq/100 g in soil, 0.07% to 0.12% in forages, 1.35 to 2.86 mg/100 ml in blood serum and 0.42% to 0.55% in bone. Mineral concentration observed in the soils, forages, bone and blood tissues determined shortages of phosphorus in the animals during four periods, calcium during one period and magnesium during three periods.